Partial purification and functional expression of brain mRNAs coding for neurotransmitter receptors and voltage-operated channels. - Sumikawa, K (1984)
Poly(A)+ mRNAs extracted from embryonic chicken brain and from adult rat brain were fractionated on sucrose density gradients. The fractions were subsequently injected into Xenopus oocytes where the mRNA was translated. The products were processed and incorporated into the oocyte membrane where they formed functional neurotransmitter receptors and voltage-operated channels. Different mRNA fractions induced the incorporation of different transmitter receptors and voltage-operated channels into the oocyte membrane. These experiments provide a useful step towards the understanding of the structure and function of neurotransmitter receptors and channels.